1964
DOI: 10.1163/26660644-03401001
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on the Distribution and Migration of Whales, based on Observations from Netherlands Ships

Abstract: Contents 5 REMARKS ON THE DISTRIBUTION AND MIGRATION OF WHALES with regard to the determination of the species than those of other observers. His data have been collected in a special table (table 5). Grateful acknowledgment is also made to Dr. S. G. BROWN (N.I.O.-Wormley-England) who was extremely helpful in reading the manuscript and suggesting a number of corrections based on a very thorough knowledge of the subject. 2. DETERMINATION OF SPECIES In the instructions given to our collaborators on board of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 5 publications
1
36
0
1
Order By: Relevance
“…Additional records for the 1950s included opportunistic sightings from weather ships ( n = 2) (Pike & McAskie, 1969) and Dutch vessels ( n = 4) (Slijper, van Utrecht & Naaktgeboren, 1964) in the GOA. Sightings from the Dutch vessels occurred over a 4‐year period (1955–58) within a 10‐degree block between 40–50°N and 170–180°W, and are not shown on any map as exact locations were not available and species identification was uncertain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional records for the 1950s included opportunistic sightings from weather ships ( n = 2) (Pike & McAskie, 1969) and Dutch vessels ( n = 4) (Slijper, van Utrecht & Naaktgeboren, 1964) in the GOA. Sightings from the Dutch vessels occurred over a 4‐year period (1955–58) within a 10‐degree block between 40–50°N and 170–180°W, and are not shown on any map as exact locations were not available and species identification was uncertain.…”
Section: Methodsmentioning
confidence: 99%
“…5). Soviet whalers caught 121 right whales in the shallow shelf waters just west of Bristol Bay in 1964 and1967 (Fig. 5).…”
Section: Sightings and Catches 1924-68mentioning
confidence: 99%
“…data). All recorded strandings of the humpback whale (n = 3) were in Northern Luzon where sightings have been reported since 1964 (Slijper et al, 1964). A stranding of an Irrawaddy dolphin in Dumangas, Iloilo, in 2006 provided the first evidence that such species was not restricted to Malampaya Sound, Palawan.…”
Section: Spatial Variation Of Strandings and Stranding Hotspotsmentioning
confidence: 99%
“…The distribution of humpback whales in the Arabian Sea is known from whaling records (Wray and Martin 1983;Mikhalev 1997), as well as observations from merchant vessels and winter surveys off the coast of Oman. Sighting and survey records have suggested that humpback whales are mostly concentrated in the shallow nearshore areas of the coast, particularly in the Gulf of Masirah and Kuria Muria Bay regions (Minton 2004), while sighting and stranding have suggested a population range including the Balochistan coast of Pakistan, Iran, Iraq (Al Robaae 1974;Braulik et al 2010), Yemen, Northern Gulf of Aden, western India and Sri Lanka (Brown 1957;Mikhalev 2000;Minton et al 2008;Reeves et al 1991;Slijper et al 1964;Yukhov 1969). Whitehead (1985) recorded humpback whale songs off the coast of Oman, which indicate that this population coincided with the Northern Hemisphere breeding cycle, with calving taking place between January and May (Mikhalev 2000;Minton et al 2008), and peaking in early March.…”
Section: Discussionmentioning
confidence: 99%
“…Brown (1957) reported that the Arabian Sea humpback whales migrate from Antarctic feeding grounds, while Slijper et al (1964) suggest that they come from the North Pacific to the Gulf of Aden near Oman, in the Persian Gulf and off Ceylon. A total of 24 winter breeding areas were determined by Rasmussen (2006), all within 30 degrees of the equator, worldwide.…”
Section: Introductionmentioning
confidence: 99%